A statistical approach for studying the spatio-temporal distribution of geolocated tweets in urban environments - Santa, Fernando (2019)
Santa, F., Henriques, R., Torres-Sospedra, J., & Pebesma, E. (2019). A statistical approach for studying the spatio-temporal distribution of geolocated tweets in urban environments. Sustainability (Switzerland), 11(3), [595]. DOI: 10.3390/su11030595